Potential Grassland types and their Ecological Succession in Rajasthan Desert - Gupta, R K; Saxena, S K (Annals of Arid Zone, 2016)
Seven potential grassland types on different habitats of Rajasthan desert have been described, (i) Sehima nervosum type is on the hills and piedmont regions (2) Dichanthium annulatum type on older alluvial flats with sandy clay loam to clay soils. (3) Cenchru8 type on well drained alluvial soils (4) Lasiurus sindicus type on loose sandy soils (5) Desmostachya bipinnata type on young alluvium. (6) Sporobolus-DichrJnthium annulatum type on on low lying heavy soils (7) Panicum turgidum type on sand dunes. Stable cis-climax associations (grassland types) and the seral communities within the associations based on surveys) conduced in the region have been discussed in the paper.